Hubungan Status Gizi, Kebiasaan Sarapan, dan Durasi Tidur Terhadap Produktivitas Pekerja PT. Sejahtera Buana Trada Sunter: Hubungan Status Gizi, Kebiasaan Sarapan, dan Durasi Tidur terhadap Produktivitas Pekerja PT. Sejahtera Buana Trada Sunter - Wiguna, Akhsan Fikri; Stefani, Megah (Amerta Nutrition, 2023)
Background: Indonesian productivity has increased by 3.1% per year over the last 25 years. Human resources are critical, and they must be of high quality. Objectives: The objective of this study was to look at the relationship of nutritional status, breakfast habits, and sleep duration on workers' productivity at PT. Sejahtera Buana Trada Sunter. Methods: The subjects in this study were 39 workers, and it was conducted in April–July 2022. This study was designed as a cross-sectional study with purposive sampling. The subjects for this study had to be between the ages of 18 and 55, employees of PT Sejahtera Buana Trada Sunter, and have worked for at least one year. Subjects who fasted to analyze their food intake were excluded from this study. The data were analyzed using the chi-square test. Primary and secondary data were used in this study. Results: The productivity of the workforce at PT. Sejahtera Buana Trada Sunter (71.8%) is high and rated as good. There is a significant relationship between worker productivity and breakfast habits (p-value = 0.003), sleep duration (p-value = 0.004), and nutritional status (p-value = 0.002). Conclusions: The study found a relationship between the productivity of PT. Sejahtera Buana Trada Sunter employees and their breakfast habits, sleep duration, and nutritional status.